Upregulated microRNA-125b-5p in patients with asthma-COPD overlap mediates oxidative stress and late apoptosis via targeting IL6R/TRIAP1 signaling - Chang, Yu-Ping; Tsai, Yi-Hsuan; Chen, Yu-Mu; Huang, Kuo-Tung; Lee, Chiu-Ping; Hsu, Po-Yuan; Chen, Hung-Chen; Lin, Meng-Chih; Chen, Yung-Che (Respiratory research, 2024)
Background Among patients with chronic obstructive pulmonary disease (COPD), some have features of both asthma and COPD—a condition categorized as asthma-COPD overlap (ACO). Our aim was to determine whether asthma- or COPD-related microRNAs (miRNAs) play a role in the pathogenesis of ACO. Methods A total of 22 healthy subjects and 27 patients with ACO were enrolled. We selected 6 miRNAs that were found to correlate with COPD and asthma. The expression of miRNAs and target genes was analyzed using quantitative reverse-transcriptase polymerase chain reaction. Cell apoptosis and intracellular reactive oxygen species production were evaluated using flow cytometry. In vitro human monocytic THP-1 cells and primary normal human bronchial epithelial (NHBE) cells under stimuli with cigarette smoke extract (CSE) or ovalbumin (OVA) allergen or both were used to verify the clinical findings. Results We identified the upregulation of miR-125b-5p in patients with ACO and in THP-1 cells stimulated with CSE plus OVA allergen. We selected 16 genes related to the miR-125b-5p pathway and found that IL6R and TRIAP1 were both downregulated in patients with ACO and in THP-1 cells stimulated with CSE plus OVA. The percentage of late apoptotic cells increased in the THP-1 cell culture model when stimulated with CSE plus OVA, and the effect was reversed by transfection with miR-125b-5p small interfering RNA (siRNA). The percentage of reactive oxygen species-producing cells increased in the NHBE cell culture model when stimulated with CSE plus OVA, and the effect was reversed by transfection with miR-125b-5p siRNA. In NHBE cells, siRNA transfection reversed the upregulation of STAT3 under CSE+OVA stimulation. Conclusions Our study revealed that upregulation of miR-125b-5p in patients with ACO mediated late apoptosis in THP-1 cells and oxidative stress in NHBE cells via targeting IL6R and TRIAP1 . STAT3 expression was also regulated by miR-125b-5p.